The demand for health care by the elderly in Kedah: Do enabling factors matter? - Samsudin, Shamzaeffa; Abdullah, Norehan; Applanaidu, Shri Dewi; Majid, Rahimah; Lim, Hock Eam; Abu Bakar, Nor'Aznin (2013)
Understanding factors that affect health care demand by the elderly is vital for the health system to be more responsive in providing care to this special group.Since health care demand studies at micro level are rather limited within Malaysia context, this research attempts to reduce the gap by focusing on elderly demand.The main objective of this paper is to identify the effect of enabling factors on health care demand by the elderly in Kedah, Malaysia.Enabling factors are factors that may support demand.We concentrate on two enabling factors which are individual total income and social capital. Informal interaction with the surrounding community is used to represent social capital.Health care demand in in this paper is measured by whether the respondents have had a doctor visit in the past one month before the interview.A multistage cluster sampling was used in selecting the sample for the study.A total of 399 of respondents aged 62 to 98 were interviewed face-to-face using a structured questionnaire.A probit model with robust variance estimates was used in estimating the demand equation.It is found that both income and social capital, after controlling for other socioeconomic and health related factors, are statistically significant in affecting demand. The higher the income is, the higher the likelihood to visit a doctor.On the other hand, the informal interaction in the society has reduced the likelihood for doctor visit.This is evident that health condition is not the only factor that determines health care demand of the elderly in Kedah state.The findings from this analysis imply that the government’s policy to reduce income inequality of the people may indirectly reduce the income-related inequity in health care demand.In addition, support programs in the community need to be intensified to raise awareness of health and consequently reduce unnecessary visits to health services.